Methadone as HIV prevention: high volume methadone sites to decrease HIV incidence rates in resource limited settings. - Bruce, R Douglas (The International journal on drug policy, 2010)
The link between injection drug use and HIV has been extensively described. Despite worldwide prevention efforts, injection drug use continues to be a risk factor for HIV transmission and both HIV and injection drug use continues to spread across the globe. Although methadone has demonstrated multiple health benefits including the reduction in injection drug use and HIV acquisition, the utilisation of methadone in many areas of the world remains one of secondary, rather than primary, HIV prevention. As a result, many who finally begin methadone enter treatment having accumulated medical and mental health problems as a result of delayed treatment. Rapid access to treatment and a more aggressive policy that realizes that methadone can help reduce opioid drug use is necessary if methadone is effectively going to act as primary HIV prevention. To delay access to methadone only increases the probability that the individual will acquire an infectious disease that is more costly to the individual in terms of morbidity and mortality and more costly to society as a whole.
Keywords: Developing Countries; Disease Outbreaks; Harm Reduction; Health Services Accessibility; HIV Infections; Humans; Incidence; Methadone; Preventive Health Services; Risk Factors; Substance Abuse, Intravenous